Pemberdayaan PKG-PAUD Kecamatan Gunungpati dalam Memanfaatkan Daur Ulang Sampah Kertas dan Plastik untuk Alat Pembelajaran - Dwi Yulianti; Pratiwi Dwijananti; Fifin Ratna Dewi; Khoirunnisa Meiah; Fafi Masiroh (Jurnal Surya Masyarakat, 2025)
Each school in Gugus PAUD 1, Gunungpati Sub-district, Semarang City already has a Waste Bank, although it is small and simple.  The waste collected comes from around the school and store from each student. The collected waste then sold to collectors. The existence of this waste bank makes it possible to recycle it into playground equipment/games or learning tools, because learning in PAUD is playing while learning. The purpose of the Community Service activities in Gugus PAUD 1 Gunungpati District Semarang City is to improve the competence of PAUD teachers in recycling paper and plastic waste into play tools and educational games. The method applied was theory and practice. Evaluation was conducted from administrative evaluation in the form of attendance and participation. Academic evaluation by project assessment then applications in the teaching and learning process. The results are PAUD teachers' skills and understanding of recycling paper and plastic waste increased after the workshop, as well as attitudes and behavior towards waste recycling increased, all in the high category.